2012
DOI: 10.1016/j.kjms.2012.05.004
|View full text |Cite
|
Sign up to set email alerts
|

Major food safety episodes in Taiwan: Implications for the necessity of international collaboration on safety assessment and management

Abstract: The major food safety episodes that occurred in Taiwan during the past decade are briefly reviewed in this paper. Among the nine major episodes surveyed, with the exception of a U.S. beef (associated with Creutzfeldt-Jakob disease)-related incident, all the others were associated with chemical toxicants. The general public, which has a layperson attitude of zero tolerance toward food safety, may panic over these food-safety-associated incidents. However, the health effects and impacts of most incidents, with t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 6 publications
(10 reference statements)
0
9
0
Order By: Relevance
“…The recent continual decrease in the availability of wild-caught fish has led to a rise in aquaculture fish production as well as a rise in their consumption. However, in Taiwan, major food safety incidents over the past decade have been related to aquatic product consumption [9] and economic losses have been incurred because the import of some Taiwanese aquacultured food products has been banned by several countries worldwide [10]. Consequently, Taiwan's government is paying increasing attention toward aquacultured product safety and quality assessment and management.…”
Section: Introductionmentioning
confidence: 99%
“…The recent continual decrease in the availability of wild-caught fish has led to a rise in aquaculture fish production as well as a rise in their consumption. However, in Taiwan, major food safety incidents over the past decade have been related to aquatic product consumption [9] and economic losses have been incurred because the import of some Taiwanese aquacultured food products has been banned by several countries worldwide [10]. Consequently, Taiwan's government is paying increasing attention toward aquacultured product safety and quality assessment and management.…”
Section: Introductionmentioning
confidence: 99%
“…Residues of pesticides and drugs were major concerns of consumers. In 2005, cases of groupers ( Epinephelus ) contaminated with malachite green, a banned drug, had severe consequences on the grouper sector in Taiwan (Li et al, : 512). Following the state regulation of the safe use of the drug and pesticides (associated with its dosage and withdrawal period), some farmers began to label their products as non‐toxic ( wu‐du ).…”
Section: Official Responses To Food Safety Fears and Rural Regeneratimentioning
confidence: 99%
“…Despite several recent papers emphasised the importance of international collaboration in the food industry, e.g. (Bombaywala and Riandita, 2015) believed that interaction, collaboration, and information sharing play an important role in innovation in the food industry, and (Li et al, 2012) concluded that international collaboration is an effective factor of food safety assessment and management, there is a lack of research on international collaboration in the entrepreneurial food industry. As evident, (Lynde, 2020) recommended that a new food system is required in which entrepreneurs require constructed broadly collaboration between shareholders.…”
Section: Introductionmentioning
confidence: 99%